Integrative Islamic Educational Thought: Comparative Analysis of Al-Ghazali and Fazlur Rahman - Sherli Dwi Andri Saputri; Duski Samad; Firdaus ST Mamad (The Future of Education Journal, 2025)
This article explores the educational thought of two influential Muslim scholars, Al-Ghazali and Fazlur Rahman, through a philosophical and comparative perspective. The study aims to analyze their concepts of Islamic education, their intellectual foundations, and the relevance of their ideas for contemporary educational development. Using a qualitative library research approach, the article examines primary and secondary sources related to both scholars and identifies the distinctive characteristics of their educational paradigms. The findings reveal that Al-Ghazali emphasizes spiritual purification, ethical formation, and the integration of knowledge and moral action, while Fazlur Rahman advocates neo-modernist reform, critical reasoning, and integration between religious and scientific knowledge. Despite their different contexts, both highlight the importance of holistic human development. This study concludes that combining Al-Ghazali’s moral–spiritual framework with Rahman’s intellectual–critical paradigm provides a relevant foundation for formulating contemporary Islamic education that is spiritually rooted, intellectually dynamic, and responsive to modern challenges.